The impact of special care newborn units on routine neonatal care practices in central India: observational study - Tripathi, Gaurav; Mishra, Neha (International Journal of Contemporary Pediatrics, 2016)
Background:To address high infant and neonatal mortality rate (NMR) in the state, government of Madhya Pradesh and UNICEF adopted continuum of care from community to health facility as the core theme. This approach was first piloted with UNICEF support in Guna in the year 2007 and is now being scaled up state wide under National Rural Health Mission (NRHM). Special care new born units (SCNU) are being set up at district levels. First two such units were set up by Government of M.P with support from UNICEF in Guna and Shivpuri districts. After the successful Janani Suraksha Yojana (JSY) scheme, IMNCI would need to respond in new born care. The main objective of scheme was to reduce NMR and improving in quality of care of neonates. The aim of the study was to evaluate the impact of creating a sick newborn care unit (SNCU) in district hospitals on new born care practices and to evaluate the contribution of SCNU of Rewa division in improved neonatal survival. Methods: Observational study was conducted during April 2014 to June 2014 at district Hospitals Satna, Sidhi, Shahdol, Umariya, Anooppur and Singrauli (high priority districts of Rewa division, Madhya Pradesh, India). Study subjects were 112 mothers of new born babies, 6 pediatricians posted in SCNU, 4 staff nurses from SCNU and 2 superintendents of hospitals. Data was collected using both qualitative and quantitative techniques by personal interview of staff and mothers of beneficiaries through preformed questionnaires. Results:There is a reduction in NMR after the implementation of SCNU. Majority of the beneficiaries are motivated and aware about the new born care and were improving their knowledge about neonatal care. Staff of SCNU given multiple responses regarding the satisfaction from the facilities, mostly say (90%) that they are satisfied of facilities ad infrastructure though the staff posted there is not sufficient for the unit. Conclusions:There is evidence that the knowledge and awareness regarding the neonatal care is improved due to the SCNU and it also contributed to the reduction in neonatal mortality rate. Most of the mothers are satisfied with the services and follow-up, which shows that SCNU helps to improve neonatal care. Majority of staff are satisfied by the infrastructure and services in spite of insufficiency in the number of staff.